MiR319‐targeted OsTCP21 and OsGAmyb regulate tillering and grain yield in rice. Issue 7 (1st June 2021) - Wang, Rongna; Yang, Xiuyan; Guo, Shuang; Wang, Zhaohui; Zhang, Zhanhui; Fang, Zhongming
Abstract: Multiple genes and microRNAs (miRNAs) improve grain yield by promoting tillering. MiR319s are known to regulate several aspects of plant development; however, whether miR319s are essential for tillering regulation remains unclear. Here, we report that miR319 is highly expressed in the basal part of rice plant at different development stages. The miR319 knockdown line Short Tandem Target Mimic 319 (STTM319) showed higher tiller bud length in seedlings under low nitrogen (N) condition and higher tiller bud number under high N condition compared with the miR319a‐overexpression line. Through targets prediction, we identified OsTCP21 and OsGAmyb as downstream targets of miR319. Moreover, OsTCP21 and OsGAmyb overexpression lines and STTM319 had increased tiller bud length and biomass, whereas both were decreased in OsTCP21 and OsGAmyb knockout lines and OE319a. These data suggest that miR319 regulates rice tiller bud development and tillering through targeting OsTCP21 and OsGAmyb . Notably, the tiller number and grain yield increased in STTM319 and overexpression lines of OsTCP21 and OsGAmyb but decreased in OE319a and knockout lines of OsTCP21 and OsGAmyb . Taken together, our findings indicate that miR319s negatively affect tiller number and grain yield by targeting OsTCP21 and OsGAmyb, revealing a novel function for miR319 in rice. Abstract : The microRNA miR319s play negative roles in regulating bud outgrowth and tiller number in rice by targeting the transcription factor genes OsTCP21 and OsGAMYB .